Grain yield of corn hybrids depends on their maturity group - Yurchenko, S.; Stepanenko, B.; Khachaturian, A. (Scientific Progress & Innovations, 2024)
The article presents the results of research on the patterns of corn yield formation depending on the individual characteristics of hybrids, growing conditions and the relationship to the FAO maturity group. Field studies were conducted during 2023–2024 on demonstration crops of corn hybrids in the Poltava region. The object of the research was 16 modern corn hybrids of different maturity groups of the Dekaib selection: 50 % were medium early (FAO 201–300), 37.5 % were medium ripe (FAO 301–400), and 12.5 % were medium late (FAO 401–500). The aim of the research was to determine the influence of maize hybrids of different maturity groups on the formation of yield and pre-harvest grain moisture content in the conditions of the Left-Bank Forest-Steppe of Ukraine. The maize hybrids used in the research revealed peculiarities of yield formation depending on the maturity group and growing conditions. Corn yields over the years of research varied widely from 9.02 t/ha to 15.28 t/ha. Hybrids of the medium-ripening group were distinguished by the level of yield: DKS 4098 (13.44 t/ha) and DKS 4712 (13.32 t/ha). In terms of pre-harvest moisture content, the lowest index was observed in hybrids: DKS 3402 (16.3 %), DKS 3400 (16.7 %), DKS 3609 (16.6 %), DKS 3805 (16.7 %). The comparative analysis of the average data of 2023–2024 resulted in the identification of maize hybrids characterised by the optimal combination of yield and pre-harvest grain moisture: DCS 3609 (12.16 t/ha; 16.6 %); DCS 3805 (12.64 t/ha; 16.7 %). The analysis of correlation coefficients revealed a weak dependence (r=+0.1299) of yield and a significant dependence (r=+0.3622) of pre-harvest grain moisture on the FAO index, indicating that the manifestation of these traits depends on the growing conditions and individual characteristics of the studied hybrids. According to the results of the field experiment, it was found that the formation of maize yields depended on the individual characteristics of the hybrid by 40.4 %, and on the weather conditions of the growing season by 31.7 %, on the interaction of the two factors by 24.5 %, and on other factors by 3.4 %.